2009
DOI: 10.1021/cm802537g
|View full text |Cite
|
Sign up to set email alerts
|

Syndiotatic Polystyrene Aerogels with β, γ, and ε Crystalline Phases

Abstract: The influence of thermal treatments and supercritical carbon dioxide extraction procedures on the crystal structure and morphology of sPS aerogels is investigated mainly by wide-angle X-ray diffraction and scanning electron microscopy. The use of supercritical CO2 extraction treatments allows the obtaining of high porosity aerogels with fibrillar morphology, not only exhibiting the nanoporous δ phase but also the dense γ and β crystalline phases. Moreover, a procedure to obtain high-porosity aerogels exhibitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
91
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(102 citation statements)
references
References 63 publications
6
91
0
Order By: Relevance
“…[35,36] The absorption rate of solvent molecules was enhanced by a porous aerogel with a mesh structure, which was prepared by treating the sPS gel in scCO2. [37][38][39] The relationship between the size of the solvent molecule and the cavity volume of e-sPS was reported by Tsujita et al [40][41][42][43] It was shown that the cavity volume of -sPS is reduced after extracting the solvent molecules.…”
Section: Introductionmentioning
confidence: 83%
“…[35,36] The absorption rate of solvent molecules was enhanced by a porous aerogel with a mesh structure, which was prepared by treating the sPS gel in scCO2. [37][38][39] The relationship between the size of the solvent molecule and the cavity volume of e-sPS was reported by Tsujita et al [40][41][42][43] It was shown that the cavity volume of -sPS is reduced after extracting the solvent molecules.…”
Section: Introductionmentioning
confidence: 83%
“…1,2 It has been shown that CO2 extraction of s-PS thermoreversible gels leads to a special class of monolithic physically crosslinked aerogels, where the crystallites that constitute the physical knots of the aerogel exhibit a nanoporous crystalline phase. [3][4][5] These nanoporous crystalline aerogels present, beside disordered amorphous mesoand macropores (typical of all aerogels), also all identical nanopores of the crystalline phases.…”
Section: Introductionmentioning
confidence: 99%
“…6 This result is due to the formation of a spherulic morphology in PPO gels rather than a fibrillar morphology as observed in s-PS gels. 3,5 However it has been shown that monolithic PPO based aerogels with nanoporous crystalline phases can easily be obtained starting from mixed PPO/s-PS gels thanks to fibrillar morphology ensured by s-PS. 6 The association of amorphous meso-and macropores and crystalline nanopores confers unique properties to this new type of material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown recently that high porosity syndiotactic polystyrene (sPS) aerogels can be obtained by supercritical CO 2 extraction of the solvent present in the native sPS physical gels [1][2][3] or by sublimation of the solvent. [4][5] The advantage of using a supercritical extraction process to remove the solvent from the gel is the absence of surface tension and in these conditions a supercritical solution is formed between supercritical CO 2 and liquid solvent.…”
Section: Introductionmentioning
confidence: 99%